Antiviral properties of Berembang Bukit and Kandis Hutan against psedorabies virus in animal cell culture - Goh, Sheen Yee; Allaudin, Zeenathul Nazariah; Tan, Seok Shin; Loh, Sandy Hwei San; Ting, Kang Nee; Mohd Lila, Mohd Azmi (2011)
Tropical rainforest in Malaysia represents and untapped potential source of antiviral compounds. Bioactive compounds in plant species from the same genus as Kandis Hutan such as xanthones, benzophenones, biflavonoids and lupeol had been studied. Eugeniin is an anti-herpesvirus compound which had also been found n Berembang Bukit. This preliminary study was carried out to discover the presence of antiviral properties in Berembang Bukit and Kandis Hutan using different antiviral assays. In this study, MTT cell viability assay was used in addition to microscopic evaluation of pseudorabies virus (PrV)- induced cytopathic effects (CPE) on Vero cells. The cellular toxicity of DMSO was also evaluated. DMSO was less than 10% cytotoxic at concentration of 0.1% to Vero cells and its effect can be negligible. Both plants had demonstrated antiviral properties in thyl acetate and ethanol extracts. From our findings from all three antiviral assays, the ethanol-extracted Kandis Hutan possessed the most promising antiviral properties. Nevertheless, antiviral potential of ethyl acetate and ethanol-extracted Berembang Bukit and ethyl acetate-extracted Kandis Hutan also merit further investigation